Fundamental solution in micropolar viscothermoelastic solids with void - Kumar, Rajneesh; Sharma, Krishan D.; Garg, S.K. (Zielona Góra: Uniwersytet Zielonogórski)
In the present article, we construct the fundamental solution to a system of differential equations in micropolar viscothermoelastic solids with voids in case of steady oscillations in terms of elementary functions. Some basic properties of the fundamental solution are also established.
Keywords: micropolar thermodiffusion; steady oscillations; visothemoelastic; micropolar with void